Nature-Based Solutions for Water and Disease Management in Banana, Plantain, and Pineapple: A Systematic Review - Gamboa-Agüero, Marcelo (2026)
Introduction: Banana, plantain, and pineapple value chains contribute significantly to the economy of Central America but face major environmental challenges. Objective: To systematize nature-based solutions applicable to water and disease management across the production, post-harvest, and processing stages of these crops, based on scientific research published during the last five years. Methods: We conducted a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. We searched articles published between 2020 and 2024 in indexed journals in SciELO and Scopus and selected forty studies. We analyzed the studies using inductive thematic analysis and complemented this approach with a deductive assessment of research origins and methodological applicability. Results: Research on water management mainly focused on the processing stage. For banana and plantain, the most frequent topics included adsorption of water contaminants, use of by-products and waste, and development of new applications. For pineapple, studies primarily addressed the use of by-products and waste. Research on disease management concentrated on banana and plantain and emphasized antagonistic microorganisms, crop and soil management practices, and natural products, including the production of antagonists from pineapple residues. Most studies relied on controlled experimental designs. Conclusion: Although the scientific literature is diverse and highlights important advances in processing-stage innovations and disease control in banana and plantain, research under field and agro-industrial conditions remains limited, particularly for pineapple.